KONTRIBUSI KEMAMPUAN MATEMATIKA PADA HASIL BELAJAR KIMIA SISWA KELAS XI SMA TERHADAP POKOK BAHASAN HIDROLISIS GARAM - Yustika Mawarini Simanjuntak; Pasar Maulim Silitonga (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2020)
This study aims to study whether there is a linear and significant relationship, which is positive and greater than mathematical abilities on student chemistry learning outcomes. The population in this study were all students of class XI MIPA of SMA Negeri 1 Lubuk Pakam which consisted of 7 classes. The research sample is one class taken by purposive technique. This study uses 15 objective test instruments that have been questioned for validity, suitability, power differences and reliability of 0.806 (high) for mathematical ability data and reliability of 0.799 (high) for chemistry learning outcome data. For the first hypothesis test results namely linearity regression test using ANAVA regression test shows Fcount> Ftable (30.7503> 4.13), for the second hypothesis test result is a comparison test using the product moment test shows rcount> rtable (0.6891> 0.329). Based on hypothesis testing, then Ho is rejected and accepted that there is a linear and significant relationship and there is a positive conflict between mathematical ability and student chemistry learning outcomes. To test the coefficient of determination determines whether the ability of mathematical agreement with student chemistry learning outcomes is 47.49% while 52.51% is influenced by other factors.